Petrología de las rocas intrusivas neógenas de Costa Rica - Kussmaul, Siegfried (2011)
The purpose of this paper is to present a synthesis of the petrology of the Neogene plutonic rocks of Costa Rica. Two series are distinguished: an alkaline one of Miocene/Pliocene age, restricted to a small area and a calc-alkaline series of Miocene and Pliocene age and with a wide areal extension. The plutonic bodies are generally small and have been emplaced during various intrusive stages near to the surface. The mineralogical composition of the calc-alkaline rocks is very uniform. There are, however great variations in their modal composition and texture, not only from one intrusive unit to another but also between the different intrusive bodies of the same unit. Chemically there exists a difference between the calc-alkaline plutonic rocks of the Cordillera de Talamanca and those of the Cordillera de Tilarán, specially with regard to the alkali content and the iron enrichment, which might be due to crustal thickening during the Upper Miocene. The origin of these cale-alkaline plutonic rocks is explained in terms of a two stage model. The first stage comprises the formation of tholeiitic and Calc-alkaline melts which are underplated. The second stage yields intermediate to acid magmas by partial melting of the increased crust.